Games of cricket and the General Resurrection - Sturch, Richard (Religious studies, 2015)
It is often objected to the Christian doctrine of the resurrection of the dead that if we reject dualism and disembodied existence there is no way even for God to bring it about that a resurrected person is identical with his or her supposed original, rather than just a duplicate. My response is that if God intended all along that people should have two periods of existence, the problem vanishes. In a Test Match, there are long periods when the ground and stands are empty and no play takes place, yet no-one says that the resumed game may only be a duplicate of that of the previous day. The same holds for a resurrection intended from the beginning.